Analyzing Academic English Writing Needs of Natural Sciences Researchers - Akhtar, Javeria; Rubab, Iram (Annals of Human and Social Sciences, 2024)
The aim of present study is to investigate the needs of English writing skills of MS Researchers of Natural Sciences disciplines of Sialkot to achieve the targets. Insights for the undertaken study were taken from the theory of Needs Analysis Hutchinson & Walters (1987). In this regard, researchers from three departments were considered: Department of Physics, Department of Chemistry and Department of Zoology. To judge the existing situation of researchers’ competence, questionnaire was used as an instrument. The questionnaire was comprised of two sections: Target Situation Analysis and Present Situation Analysis; was given to all researchers (n=120) of these departments. Findings reflect the existing situation of the researchers regarding writing skills is not satisfactory to cope up the research based activities. To overcome this problem, they are in need of EAP course to improve their writing skills.